Kritik Nalar Hermeneutika Paul Ricoeur - Daden Robi Rahman (Universitas Darussalam Gontor, 2016)
Hermeneutics was born and developed in the West, specifically in response to the theological problem of Christianity, and always claimed to be an effective solution to the interpretation of Scripture. With existence of various schools, hermeneutics has also various shades and resulted different interpretations. Such as Schleiermacher, followed by Wilhelm Dilthey and Emilio Betti as initiators of hermeneutics methodology. Martin Heidegger and Gadamer followed with their ontological hermeneutics, and continued by Habermas with his critical hermeneutics. After that, the critical ontological hermeneutics initiated by either Paul Ricoeur, or Rudolf Bultman with his theological hermeneutics, and Derrida with his deconstructive hermeneutics. Among those schools, the writers interested in reviewing the hermeneutics of Paul Ricoeur which represents a distinctive theory of interpretation. His idea considered to be a bridge of the fierce debate between methodological traditions and philosophical traditions represented by Emilio Betti and Hans Georg Gadamer. The thought of Ricoeur was also claimed as a mediator between the positions of the romantic tradition of Schleiermacher and Dilthey with philosophy hermeneutic by Martin Heidegger. In another side, he was placed as a combination between the two great philosophical tradition, that’s German phenomenology and France structuralism. Furthermore, the thought of Ricoeur is a revision to the thought of Dilthey about explanation (erklären) and understanding (verstehen). Through this paper, the writer will attempt to unravel the thought of Paul Ricoeur, and in the end, will clearly known the position of Ricoeur among other hermeneutics initiators.